Population pharmacokinetic analysis, renal safety, and dosing optimization of polymyxin B in lung transplant recipients with pneumonia: A prospective study - Cai, Xiao-Jun; Chen, Yan; Zhang, Xiao-Shan; Wang, Yu-Zhen; Zhou, Wen-Bo; Zhang, Chun-Hong; Wu, Bo; Song, Hui-Zhu; Yang, Hang; Yu, Xu-Ben (Frontiers in Pharmacology, 2022)
Objectives: This study aims to characterize the population pharmacokinetics of polymyxin B in lung transplant recipients and optimize its dosage regimens. Patients and methods: This prospective study involved carbapenem-resistant organisms-infected patients treated with polymyxin B. The population pharmacokinetic model was developed using the NONMEM program. The clinical outcomes including clinical treatment efficacy, microbiological efficacy, nephrotoxicity, and hyperpigmentation were assessed. Monte Carlo simulation was performed to calculate the probability of target attainment in patients with normal or decreased renal function. Results: A total of 34 hospitalized adult patients were included. 29 (85.29%) patients were considered of clinical cure or improvement; 14 (41.18%) patients had successful bacteria elimination at the end of the treatment. Meanwhile, 5 (14.71%) patients developed polymyxin B-induced nephrotoxicity; 19 (55.88%) patients developed skin hyperpigmentation. A total of 164 concentrations with a range of 0.56–11.66 mg/L were obtained for pharmacokinetic modeling. The pharmacokinetic characteristic of polymyxin B was well described by a 1-compartment model with linear elimination, and only creatinine clearance was identified as a covariate on the clearance of polymyxin B. Monte Carlo simulations indicated an adjusted dosage regimen might be needed in patients with renal insufficiency and the currently recommended dose regimens by the label sheet of polymyxin B may likely generate a subtherapeutic exposure for MIC = 2 mg/L. Conclusion: Renal function has a significant effect on the clearance of polymyxin B in lung transplant recipients, and an adjustment of dosage was needed in patients with renal impairments.